Structure Characterization and Biodegradation Rate of Poly(ε-caprolactone)/Starch Blends - Nevoralová, Martina; Koutný, Marek; Ujčić, Aleksandra; Starý, Zdeněk; Šerá, Jana; Vlková, Helena; Šlouf, Miroslav; Fortelný, Ivan; Kruliš, Zdeněk (Frontiers in Materials, 2020)
The present paper focuses on the effect of blending poly(ε -caprolactone) (PCL) with thermoplastic starch (TPS) on the final biodegradation rate of PCL/TPS blends emphasizing the type of environment, in which biodegradation takes place. The blends were prepared by melt-mixing of the components while before that a two-step processing procedure which strongly affects the degree of plasticization and thereby final material morphology, as was detailed described in the previous work, was used for the thermoplastic starch. Concentration row of pure PCL over PCL / TPS blends to pure TPS was analyzed for biodegradation in two different environments (compost and soil) as well as from morphological, thermomechanical, rheological and mechanical point of view. The morphology of all samples was studied before and after biodegradation. The biodegradation rate of the materials was expressed as the percentage of carbon mineralization and significant changes, especially after exposure in soil, were recorded. The crystallinity of the measured samples indicated that the addition of thermoplastic starch has a negligible effect on PCL-crystallization. The blend with 70% of TPS and a co-continuous morphology demonstrated very fast biodegradation with the initial rate almost identical to pure TPS in both environments while the 30% TPS blend exhibited particle morphology of starch phase in PCL matrix which probably resulted in a dominant effect of the matrix on biodegradation course. Moreover, some molecular interaction between PCL and TPS as well as differences in flow and mechanical behavior of the blends was determined.